The Effectiveness of Video and Leaflet Media on Mothers' Knowledge, Attitudes, And Behavior in Stunting Prevention Efforts at Puskesmas Karangmojo II - Silviatul Amalia; Ismarwati; Dewi Rokhanawati (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Stunting is a global challenges and issues faced by societies around the world. The prevalence of stunting in the world is 148.1 million or 22.3%. The highest incidence of stunting is in Asian countries (52%) and African countries (43%). Stunting causes morbidity and mortality. Objective: to analyze the effectiveness of video and Leaflet media on mothers' knowledge, attitudes, and behavior to prevent stunting. Method: This quasi-experiment study used a non-equivalent control group design. It involved 32 mothers who have low birth weight babies (LBW) selected using purposive sampling techniques. Prior to its use, the questionnaire was subjected to tests of validity and reliability. The collected data were subsequently analyzed using statistical techniques, specifically paired t-tests and independent samples t-tests. Results: video and leaflet media effectively increased mothers' knowledge, attitudes, and behavior with a sig value of p = 0.000. The intervention group got the highest score with an average value of 15.62, 12.00, and 13.44 for knowledge, attitude, and behavior respectively. There was no significant difference in mothers’ knowledge (0.522), attitude (0.052), and behavior (0.476). Multiple Regression Analysis with a dummy on age, education and occupation did not influence mothers’ knowledge, attitude, and behavior to prevent stunting. Conclusions: Videos and leaflets effectively improve mothers' knowledge, attitudes, and behaviors towards stunting prevention efforts at Puskesmas Karangmojo II. however, no significant difference was found between the two grous. Keywords: Knowledge; Attitudes; Behaviors; Mothers; Stunting; Prevention